PENERAPAN TES FORMATIF DALAM METODE PEMBELAJARAN KOOPERATIF - DINAR PRATAMA (Jurnal Evaluasi Pendidikan, 2012)
This study is aimed at examining the influence of both learning models used in the classroom and formative test occurrence towards students’ achievement in English. The design used was the factorial design of 2 x 2. Research result showed that The students’ achievement in English who were given the TGT learning model was higher than the students’ who were given the NHT learning model, The students` achievement in English who were given the test more frequent was higher than the students’ who were given the test lesser, there was an interaction effect between both learning models applied to the students and the formative test occurrence given to students towards the students` achievement in English, the students who were given more frequent formative test and the TGT learning model gave higher score in their English achievement than the students’ who got the NHT learning model, meanwhile the students who got TGT learning model and were given less frequent formative tests gave higher score than the students who were given less frequent formative test.